Solitary fibrous tumor of the liver. Report of three cases of a very rare tumor. Issue 7 (4th July 2018) - Barbosa, Berta; Morais, Catarina; Neves, Sílvia; Canha, António; Soares, Paulo; Daniel, Jorge; Silva, Donzilia Sousa; Davide, José
Abstract: Introduction: Solitary fibrous tumors (SFT) can originate in any site of the body. Hepatic location is extremely rare. Presentation: We present three cases corresponding to women of 26, 40 and 78 years old, with the diagnose of a liver tumor, compatible with SFT, discovered on abdominal CT, who were submitted to right, left and atypical hepatectomy, respectively. The first patient has undergone multiple interventions for excision of metastatic lesions, and is stable with trabectedin; the second patient is asymptomatic with no evidence of recurrence; the third patient had recurrence of the disease after 16 months and passed away 32 months after diagnosis. Conclusion: Hepatic malignant SFT is very rare, although should be consider in the differential diagnosis of a single large hepatic tumor. Definitive diagnosis is based on histopathological and immunohistochemical findings; surgery remains the mainstay of treatment and careful follow-up is advised.